In vitro antioxidant and antibacterial activities of extracts from Yemen aromatic plants - Riyadh abdulmajid Saheh Thabit; Xiang-Rong Cheng; Nabil Al-Hajj; Xue Tang; Guo-Wei Le (International Journal of Phytomedicine, 2013)
The aim of this work was to (i) determine the antioxidant activity in the extracts of five Yemeni plants: Zizyphus vulgaris, Thymus vulgaris, Ruta graveolens, Lavandula officinalis, and Salavia officinalis by two different antioxidant test 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and β-Carotene bleaching (BCB); (ii) determine the total phenolic (TP), total flavonoids (TF), total tannins (TT), and total anthocyanins (TA) of the extracts by Folin-Ciocalteu method, aluminium chloride method, Folin and Ciocalteu method, and pH-differential method, respectively; (iii) investigate the effectiveness of the extracts on the growth inhibition of some indicators of foodborne illness bacteria by agar well diffusion assay. There is a great variability in the TP, TF, TT, TA, inhibition of DPPH and BCB, and antibacterial effectiveness of the extraction obtained from the five plants. S. officinalis and L. officinalis best inhibition of DPPH (60.42%, 43.97%), BCB (80.77%, 67.77%), possessed the highest TP (75.2, 64.9 mg/g) and TT (0.70, 0.66 mg/g), while the Z. vulgaris possessed the highest TF (48.1 mg/g) and TA (0.49 mg/100g ). The extracts of R. graveolens exhibited inhibitory effects against most tested bacteria at all added doses.